Vaksinasi Covid 19 sebagai Upaya Peningkatan Status Kesehatan bagi Masyarakat Kecamatan Mojotengah, Wonosobo - Marwiati Marwiati; Ari Setyawati; Ujang Sauban (Universitas Mathla'ul Anwar Banten, 2021)
COVID-19 VACCINATION AS AN EFFORT TO IMPROVE COMMUNITY HEALTH STATUS IN MOJOTENGAH WONOSOBO. Covid-19 is a disease caused by infection with the SARS COV II virus which attacks the human respiratory system. This disease causes sufferers to experience shortness of breath, hypoxia which results in respiratory system failure. Immunization is carried out as one of the government's efforts to end the Covid-19 pandemic in Indonesia. Covid-19 vaccination is the provision of an antigen in the form of a weakened Covid-19 virus. Participants were enthusiastic about vaccinating. There were no AEFI (KIPI) incidents for all participants. Education related to healthy living habits is still carried out, even though vaccinations have been carried out, they still have to maintain health protocols, a clean and healthy lifestyle and implement 5M, so that people can live healthily during a pandemic and are expected to be free from Covid-19 infection.